Methodology for the digitalization of advertisement at the point of sale for gross margin increase in the traditional retail trade - Cheng-Fong, Luis (2019)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.